2006
DOI: 10.1155/2006/806874
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Numbers of Community Cases of Illness Due to Salmonella, Campylobacter and Verotoxigenic Escherichia Coli: Pathogen‐Specific Community Rates

Abstract: The authors estimate that a significant number of infections due to VTEC, Salmonella and Campylobacter occur each year in Canada, highlighting the fact that these enteric pathogens still pose a significant health burden. Recognizing the significant amount of under-reporting is essential to designing appropriate interventions and assessing the impact of these pathogens in the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 31 publications
1
73
0
2
Order By: Relevance
“…Other authors have previously reported similar studies to reconstruct the surveillance pyramid for specific pathogens or for gastrointestinal illness in general [1,9,[11][12][13]33]. The current study is more comprehensive than previous studies, considering seven enteric pathogens in seven countries.…”
Section: Comparison With Other Reconstruction Studiesmentioning
confidence: 94%
“…Other authors have previously reported similar studies to reconstruct the surveillance pyramid for specific pathogens or for gastrointestinal illness in general [1,9,[11][12][13]33]. The current study is more comprehensive than previous studies, considering seven enteric pathogens in seven countries.…”
Section: Comparison With Other Reconstruction Studiesmentioning
confidence: 94%
“…Salmonellosis is significantly underreported; therefore, it is very difficult to precisely determine the actual public health burden of Salmonella worldwide (59). Canadian studies suggest that the ratio of salmonellosis infections per reported case ranges from 13 to 37, highlighting the need to develop rapid, accessible, and economical assays to facilitate clinical diagnosis and reporting strategies (62).…”
mentioning
confidence: 99%
“…In Quebec province alone, nearly 3,000 cases of diarrheal illness are attributed annually to Campylobacter enteritis, more than the combined total caused by Salmonella and Shigella species, Escherichia coli O157:H7, and Yersinia enterocolitica (15). Thomas et al recently concluded that even these numbers appear to represent a substantial underestimate of the public health burden of this enteric pathogen and that for every case of Campylobacter infection reported in Canada each year, there are an additional 23 to 49 unreported cases (47).…”
mentioning
confidence: 99%